Energy integration and optimisation for sustainable total site, process and equipment design. (1st November 2019) - Walmsley, Timothy Gordon; Varbanov, Petar Sabev; Aviso, Kathleen; You, Fengqi
Abstract: The current Virtual Special Issue of the Energy Journal contains cutting-edge developments in energy research that were presented at the 21st Conference on Process Integration for Energy Saving and Pollution Reduction, held in Prague, Czech Republic, on 25–29 August 2018. Conference PRES hosted more than 234 oral and 221 poster presentations. Out of these papers, the 34 contributions in this VSI represent a selection of the most significant developments in the area of energy research, and each article includes extensions and additional results beyond the conference paper. Conference PRES is an annual symposium that aims to attract thought-leaders and academics to facilitate an ongoing discussion around energy, the impact on the environment, and the way forward. This paper provides an overview of each contribution, the context of their development, and groups them into four research themes: (1) Heat Exchangers and Heat Exchanger Networks, (2) System Optimisation, (3) System Design and Analysis, and (4) Process and System Synthesis.